High-strength and high-toughness ultrathin dry film protective film and preparation method thereof

By adopting a three-layer structure high-strength, high-strength, ultra-thin dry film protective film, low-density polyethylene, cross-linked polyethylene, cyclic polyolefin and modified montmorillonite, combining low-density polyethylene and metallocene polyethylene, using a combination of low-density polyethylene and metallocene polyethylene , the hierarchical structure of cyclic polyolefin and diatomaceous earth solves the problems of water and oxygen transmittance and mechanical properties caused by the reduction of the thickness of the dry film protective film, achieves excellent barrier and processing performance, and improves production efficiency and quality.

CN119116508AActive Publication Date: 2024-12-13湖北慧狮塑业股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411502161.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-13
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

When the existing dry film protective film decreases its thickness, the water and oxygen transmittance increases and the mechanical properties decrease, resulting in production efficiency and quality problems, and processing difficulty increases, making defect control difficult.

Method used

High-strength, high-tough ultra-thin dry film protective film with a three-layer structure, a core layer composed of low-density polyethylene, cross-linked polyethylene, cyclic polyolefin and modified montmorillonite, combining low-density polyethylene and metallocene poly The bonding layer and back layer of ethylene, cyclic polyolefin and diatomaceous earth achieve excellent water-oxygen barrier and mechanical properties through specific modified montmorillonite preparation methods and preparation processes.

Benefits of technology

The thickness of the dry film protective film was successfully reduced to below 17μm, while maintaining excellent water-oxygen barrier properties, mechanical properties and processing properties, improving production efficiency and product quality, and ensuring the curing rate and quality of the photosensitive dry film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102892360000151
    Figure BDA0005102892360000151
Patent Text Reader

Abstract

The invention discloses a high-strength high-toughness ultrathin dry film protective film and a preparation method thereof, and relates to the field of dry film protective films.The protective film is formed by compounding an attaching layer, a core layer and a back layer, the core layer is located between the attaching layer and the back layer, and the core layer is prepared from 40-70 parts of low-density polyethylene, 10-20 parts of crosslinked polyethylene, 20-40 parts of cyclic polyolefin and 3-10 parts of modified montmorillonite; the protective film has excellent water-oxygen barrier property, effectively prevents the dry film layer from being eroded by oxygen and moisture, and ensures the curing rate and quality of the photosensitive dry film; the unique three-layer structure and material combination endow the protective film with excellent mechanical properties, including high tensile strength and elongation at break, and ensure that the protective film is not broken or deformed in the stripping process; in addition, the protective film also has good processability and high yield, effectively solves the problems of high processing difficulty, difficulty in defect control and the like of the ultrathin film, and improves the production efficiency and the product quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of dry film protective films, and in particular to a high-strength and high-toughness ultra-thin dry film protective film and a preparation method thereof. Background Art

[0002] Dry film protective film is a key component in the manufacturing process of photosensitive dry film, usually composed of three layers: polyolefin dry film protective film, middle photosensitive dry film layer and PET carrier protective layer. Among them, the polyolefin dry film protective film plays a vital role in protecting the photosensitive dry film layer from oxygen and moisture erosion.

[0003] The photosensitive dry film layer is a colloidal polymer compound that is sensitive to ultraviolet rays and is mainly used for precise etching of circuit boards. Under ultraviolet rays, the dry film layer undergoes a polymerization reaction to form a stable substance that does not react with the etching solution. However, the chemical composition of the dry film is extremely sensitive to oxygen and moisture. Excessive water vapor and oxygen will cause the performance of the photosensitive adhesive to deteriorate, reduce the exposure rate, and seriously affect the curing rate of the dry film. Therefore, the industry has very strict control over the water and oxygen permeability of polyolefin dry film protective films.

[0004] Chinese patent document CN107696652A discloses a protective film for a photosensitive dry film, which is prepared by a multi-layer co-extrusion casting method or a multi-layer co-extrusion stretching method. The protective film includes a middle PP layer and two surface layers, one of which is a PE release layer, and the other is an anti-slip layer; the middle PP layer is completely prepared from PP material; the PE release layer is completely prepared from PE material, and no release agent is added to the surface of the release layer; the anti-slip layer is completely prepared from PE material, or is prepared from a copolymer or blend of PP material and PE material.

[0005] At present, the dry film protective film on the market is mainly produced by the blown film method and the cast film method, and the thickness is usually between 17 and 28 μm, of which 19 μm is the most common. However, for the sake of energy conservation, environmental protection and cost reduction, the industry is seeking ways to further thin the dry film protective film. Reducing the thickness to less than 17 μm can significantly reduce the product weight and use cost per square meter.

[0006] However, directly reducing the thickness will bring a series of technical challenges:

[0007] 1. Increased water and oxygen permeability: This will have an adverse effect on the curing rate of the dry film.

[0008] 2. Reduced mechanical properties: The protective film is easily deformed and broken when peeling, affecting production efficiency. At the same time, the protective film with reduced mechanical properties is easy to shrink and deform after being attached to the photosensitive dry film adhesive, affecting the thickness of the photosensitive adhesive layer, and further affecting the quality and use of the dry film.

[0009] 3. Increased processing difficulty: higher requirements are placed on the control of defects such as crystal points, foreign matter, and oil stains. Especially under blow molding process conditions, uneven thickness is more likely to cause film breakage.

[0010] 4. Reduced yield and output efficiency: Since the continuous winding length of the finished roll is required to be long, the above defects reduce the yield and overall output efficiency of the dry film protective film.

[0011] In addition, the dry film protective film needs to have sufficient adhesion to adhere closely to the dry film surface and reduce the contact between the dry film and the air. At the same time, it needs to have high tensile strength and elongation at break when peeling off to ensure that it will not break and affect the use efficiency.

[0012] Therefore, the development of a high-strength and high-toughness ultra-thin dry film protective film that can meet the ultra-thin requirements (thickness less than 17μm) while maintaining excellent water and oxygen barrier properties, good mechanical properties and processing properties, as well as the corresponding preparation method, has important practical significance and market value. Summary of the invention

[0013] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a high-strength and high-toughness ultra-thin dry film protective film and a preparation method thereof. The protective film has excellent water and oxygen barrier properties, effectively preventing the dry film layer from being corroded by oxygen and moisture, and ensuring the curing rate and quality of the photosensitive dry film; the unique three-layer structure and material combination give the protective film excellent mechanical properties, including high tensile strength and elongation at break, ensuring that it will not break or deform during the peeling process. In addition, the protective film of the present invention also has good processing performance and high yield, effectively solving the problems of difficulty in ultra-thin film processing and difficulty in defect control, and improving production efficiency and product quality.

[0014] In order to achieve the above object, the present invention adopts the following technical solution:

[0015] A high-strength and high-toughness ultra-thin dry film protective film is composited by a laminating layer, a core layer, and a back layer. The core layer is located between the laminating layer and the back layer, and the core layer is made of the following components by weight: 40 to 70 parts of low-density polyethylene, 10 to 20 parts of cross-linked polyethylene, 20 to 40 parts of cyclic polyolefin, and 3 to 10 parts of modified montmorillonite.

[0016] Preferably, the laminating layer is made of the following components by weight: 10 to 30 parts of low-density polyethylene, 50 to 80 parts of metallocene polyethylene, 10 to 20 parts of cyclic polyolefin, and 0.1 to 0.5 parts of diatomaceous earth;

[0017] Preferably, the back layer is made of the following components by weight: 10 to 30 parts of low-density polyethylene, 50 to 80 parts of metallocene polyethylene, 10 to 20 parts of cyclic polyolefin, and 0.1 to 0.5 parts of diatomaceous earth.

[0018] Preferably, the molecular weight of the low-density polyethylene is 100,000 to 300,000; the molecular weight of the cyclic polyolefin is 8,000 to 30,000, and the glass transition temperature is 50 to 160°C;

[0019] Preferably, the preparation method of the cross-linked polyethylene is: cross-linking low-density polyethylene powder with a particle size of 0.5 to 1 μm and a melt index of 2 to 4 g / min by electron beam irradiation technology to prepare a cross-linked polyethylene powder with a particle size of 0.5 to 1 μm.

[0020] Preferably, the total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 5 to 50% of the total thickness; and the thickness of the back layer is 5 to 50% of the total thickness.

[0021] Specifically, the thickness of the laminating layer may be 5, 10, 15, 20, 25, 30, 35, 40, 45, 50% of the total thickness;

[0022] Specifically, the thickness of the back layer may be 5, 10, 15, 20, 25, 30, 35, 40, 45, 50% of the total thickness;

[0023] Preferably, the preparation method of the modified montmorillonite comprises the following steps:

[0024] (1) calcining montmorillonite and then cooling it to room temperature to obtain activated montmorillonite;

[0025] Activated montmorillonite: Calcinate the montmorillonite and cool it to room temperature. During the calcination process, the high temperature causes the structural water in the montmorillonite to separate, increasing its specific surface area and porosity. This process destroys part of the montmorillonite crystal structure, exposing more active sites, thereby increasing its reactivity.

[0026] Preferably, in step (1), the calcination conditions are calcination at 500-600° C. in an air atmosphere for 2-3 hours.

[0027] Specifically, in step (1), the calcination temperature can be 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, or 600° C., and the reaction time can be 2, 2.5, or 3 h.

[0028] (2) adding activated montmorillonite and hexadecyl succinic anhydride to toluene, stirring and reacting under nitrogen protection, centrifuging, washing with alcohol, and drying the product to obtain anhydride montmorillonite;

[0029] Anhydride modification: The activated montmorillonite is reacted with hexadecyl succinic anhydride in toluene. The anhydride groups in the hexadecyl succinic anhydride react with the hydroxyl groups on the surface of the montmorillonite to form ester bonds on the surface of the montmorillonite while introducing carboxyl groups and long-chain alkyl groups. This process increases the hydrophobicity of the montmorillonite and introduces new reaction sites (carboxyl groups) on the surface. The nitrogen protection environment can prevent the interference of moisture and oxygen and improve the reaction efficiency.

[0030] Preferably, in step (2), the ratio of activated montmorillonite to hexadecyl succinic anhydride is 10 g:6.5-12.9 g.

[0031] Preferably, in step (2), the stirring reaction conditions are 70-80° C. for 6-8 h, and ultrasonic treatment is performed simultaneously.

[0032] Specifically, in step (2), the stirring reaction temperature can be 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, or 80° C., and the stirring reaction time can be 6, 7, or 8 h.

[0033] (3) Anhydride-modified montmorillonite and perfluorodecanol are added to tetrahydrofuran, and then 4-dimethylaminopyridine is added, and the mixture is refluxed under a nitrogen atmosphere. The product is centrifuged, washed with alcohol, and dried to obtain modified montmorillonite.

[0034] Fluorination modification: Anhydride-modified montmorillonite is reacted with perfluorodecanol in tetrahydrofuran, using 4-dimethylaminopyridine as a catalyst. In this stage, the hydroxyl group of perfluorodecanol undergoes esterification reaction with the carboxyl group introduced in the second stage under the action of the catalyst. This process introduces perfluoroalkyl chains on the surface of montmorillonite, further enhancing its hydrophobicity. Nitrogen atmosphere is also used to protect the reaction environment and prevent side reactions.

[0035] Preferably, in step (3), the ratio of anhydride montmorillonite to perfluorodecanol is 10 g:9.3-13.9 g, and the amount of 4-dimethylaminopyridine is 5-10 wt % of the perfluorodecanol.

[0036] Preferably, in step (3), the reflux reaction conditions are 60-65° C. for 6-9 hours with strong stirring.

[0037] Specifically, in step (3), the reflux reaction temperature can be 60, 61, 62, 63, 64, or 65° C., and the reflux reaction time can be 6, 7, 8, or 9 h.

[0038] The present invention also claims protection for a method for preparing the high-strength and high-toughness ultra-thin dry film protective film, comprising the following steps: mixing the raw materials according to the formula and melting them respectively through three single-screw extruders, forming a film through a batching block connector, a die head co-extrusion and cooling, and subsequently cooling and shaping the product, thickness detection, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The present invention provides a high-strength and high-toughness ultra-thin dry film protective film, which successfully reduces the thickness to below 17μm while maintaining excellent comprehensive performance. The core layer adopts a combination of low-density polyethylene, cross-linked polyethylene, cyclic polyolefin and modified montmorillonite to achieve a balance between strength and toughness. Among them, low-density polyethylene provides good flexibility and processing performance, cross-linked polyethylene enhances the strength and thermal stability of the material, cyclic polyolefin improves the barrier performance and transparency, and modified montmorillonite significantly improves the water and oxygen barrier performance. The laminating layer and the back layer adopt a combination of low-density polyethylene, metallocene polyethylene, cyclic polyolefin and diatomaceous earth, among which metallocene polyethylene provides excellent adhesion and peel strength, cyclic polyolefin enhances heat resistance and dimensional stability, and diatomaceous earth improves the slippery performance. The synergistic effect of this multi-layer structure and material formula gives the protective film excellent water and oxygen barrier properties, effectively prevents the dry film layer from being eroded by oxygen and moisture, and ensures the curing rate and quality of the photosensitive dry film. At the same time, it provides excellent mechanical properties, including high tensile strength and elongation at break, ensuring that it will not break or deform during the peeling process. In addition, the protective film of the present invention also has good processing performance and high yield, effectively solving the problems of difficulty in ultra-thin film processing and defect control, and improving production efficiency and product quality.

[0041] 2. The present invention provides a method for preparing modified montmorillonite. First, high-temperature calcination activates montmorillonite, which effectively increases the interlayer distance of montmorillonite, increases the specific surface area, and increases the number of its surface active functional groups, laying the foundation for subsequent modification. The subsequent anhydride reaction grafts long-chain alkyl groups on the surface of montmorillonite, significantly improving the compatibility of montmorillonite with organic matrices. The final esterification reaction introduces fluorine-containing groups, further enhancing the hydrophobicity of montmorillonite. This multi-step modification process enables montmorillonite to obtain a unique interlayer structure and surface properties, transforming from hydrophilicity to highly hydrophobicity while retaining the original layered structural characteristics.

[0042] 3. The present invention provides a modified montmorillonite. The lamellar structure of montmorillonite prolongs the gas diffusion path and effectively blocks the penetration of water and oxygen. Hexadecyl succinic anhydride is then grafted to introduce long-chain alkyl groups into the surface of montmorillonite, thereby improving the compatibility between montmorillonite and the resin matrix. Long-chain alkanes can also interfere with the diffusion of water vapor. Finally, perfluorodecanol is grafted to further enhance its hydrophobicity, slow down the speed at which water molecules enter the matrix, and synergistically enhance the barrier properties of the film. Secondly, the modified montmorillonite also improves the binding force with the resin, enhances the mechanical strength of the polymer matrix, improves the ductility, tensile strength and tear resistance of the protective film, and significantly improves the thermal stability and chemical resistance of the material, thereby extending the service life of the protective film. The protective film of the present invention achieves a comprehensive improvement in mechanical properties and barrier properties while maintaining ultra-thin characteristics, thereby meeting the various requirements of high-performance dry film protective films. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0044] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0045] Metallocene polyethylene includes but is not limited to ExxonMobil Chemical's EXCEED series, such as 1018, 2018, 3518 and 6026; Mitsui Chemicals' SP1540, SP2040 and SP0540 series;

[0046] Diatomaceous earth was purchased from Hebei Jiegui Mineral Products Co., Ltd., with a mesh size of 325 to 500 meshes.

[0047] A method for preparing a high-strength and high-toughness ultra-thin dry film protective film comprises the following steps:

[0048] (1) calcining montmorillonite at 500-600° C. in an air atmosphere for 2-3 h, and then cooling to room temperature to obtain activated montmorillonite;

[0049] (2) adding 10 g of activated montmorillonite and 6.5-12.9 g of hexadecylsuccinic anhydride to 100 mL of toluene, stirring and reacting for 6-8 h at 70-80° C. in a nitrogen atmosphere, and simultaneously performing ultrasonic treatment, centrifuging, washing with alcohol, and drying the product to obtain anhydride montmorillonite;

[0050] (3) adding 10 g of anhydride-modified montmorillonite and 9.3-13.9 g of perfluorodecanol to 100 mL of tetrahydrofuran, and then adding 0.465-1.39 g of 4-dimethylaminopyridine, reflux reaction at 60-65° C. in a nitrogen atmosphere for 6-9 h, while vigorously stirring, centrifuging the product, washing with alcohol, and drying to obtain modified montmorillonite;

[0051] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

[0052] The core layer is made of the following components in parts by weight: 40-70 parts of low-density polyethylene, 10-20 parts of cross-linked polyethylene, 20-40 parts of cyclic polyolefin, and 3-10 parts of modified montmorillonite; the laminating layer is made of the following components in parts by weight: 10-30 parts of low-density polyethylene, 50-80 parts of metallocene polyethylene, 10-20 parts of cyclic polyolefin, and 0.1-0.5 parts of diatomaceous earth; the back layer is made of the following components in parts by weight: 10-30 parts of low-density polyethylene, 50-80 parts of metallocene polyethylene, 10-20 parts of cyclic polyolefin, and 0.1-0.5 parts of diatomaceous earth.

[0053] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 5 to 50% of the total thickness; and the thickness of the back layer is 5 to 50% of the total thickness.

[0054] The present invention will be further described below through specific embodiments.

[0055] Example 1

[0056] A method for preparing a high-strength and high-toughness ultra-thin dry film protective film comprises the following steps:

[0057] (1) calcining montmorillonite at 600° C. in an air atmosphere for 2 h, and then cooling to room temperature to obtain activated montmorillonite;

[0058] (2) adding 10 g of activated montmorillonite and 12.9 g of hexadecylsuccinic anhydride to 100 mL of toluene, stirring and reacting for 6 h at 80° C. under a nitrogen atmosphere, and simultaneously performing ultrasonic treatment, centrifuging the product, washing with alcohol, and drying to obtain anhydride montmorillonite;

[0059] (3) 10 g of anhydride-modified montmorillonite and 13.9 g of perfluorodecanol were added to 100 mL of tetrahydrofuran, and then 1.39 g of 4-dimethylaminopyridine was added. The mixture was refluxed at 65 °C for 6 h under a nitrogen atmosphere while being vigorously stirred. The product was centrifuged, washed with alcohol, and dried to obtain modified montmorillonite.

[0060] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

[0061] The core layer is made of the following components: 70g of low-density polyethylene, 20g of cross-linked polyethylene, 40g of cyclic polyolefin, and 10g of modified montmorillonite; the laminating layer is made of the following components: 30g of low-density polyethylene, 80g of metallocene polyethylene, 20g of cyclic polyolefin, and 0.5g of diatomaceous earth; the back layer is made of the following components: 30g of low-density polyethylene, 80g of metallocene polyethylene, 20g of cyclic polyolefin, and 0.5g of diatomaceous earth.

[0062] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 30% of the total thickness; and the thickness of the back layer is 40% of the total thickness.

[0063] Example 2

[0064] A method for preparing a high-strength and high-toughness ultra-thin dry film protective film comprises the following steps:

[0065] (1) calcining montmorillonite at 560° C. in an air atmosphere for 2.5 h, and then cooling to room temperature to obtain activated montmorillonite;

[0066] (2) adding 10 g of activated montmorillonite and 10.8 g of hexadecylsuccinic anhydride to 100 mL of toluene, stirring and reacting for 7 h at 77 °C under a nitrogen atmosphere, and simultaneously performing ultrasonic treatment, centrifuging, washing with alcohol, and drying the product to obtain anhydride montmorillonite;

[0067] (3) 10 g of anhydride-modified montmorillonite and 12.4 g of perfluorodecanol were added to 100 mL of tetrahydrofuran, and then 1.08 g of 4-dimethylaminopyridine was added. The mixture was refluxed at 64 °C for 7 h under a nitrogen atmosphere while being vigorously stirred. The product was centrifuged, washed with alcohol, and dried to obtain modified montmorillonite.

[0068] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

[0069] The core layer is made of the following components: 60g low-density polyethylene, 16g cross-linked polyethylene, 34g cyclic polyolefin, and 8g modified montmorillonite; the bonding layer is made of the following components: 26g low-density polyethylene, 70g metallocene polyethylene, 17g cyclic polyolefin, and 0.4g diatomaceous earth; the back layer is made of the following components: 24g low-density polyethylene, 70g metallocene polyethylene, 16g cyclic polyolefin, and 0.4g diatomaceous earth.

[0070] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 30% of the total thickness; and the thickness of the back layer is 40% of the total thickness.

[0071] Example 3

[0072] A method for preparing a high-strength and high-toughness ultra-thin dry film protective film comprises the following steps:

[0073] (1) calcining montmorillonite at 520° C. in an air atmosphere for 2.5 h, and then cooling to room temperature to obtain activated montmorillonite;

[0074] (2) adding 10 g of activated montmorillonite and 8.6 g of hexadecylsuccinic anhydride to 100 mL of toluene, stirring and reacting for 7 h at 74 °C under a nitrogen atmosphere, and simultaneously performing ultrasonic treatment, centrifuging, washing with alcohol, and drying the product to obtain anhydride montmorillonite;

[0075] (3) 10 g of anhydride-modified montmorillonite and 10.8 g of perfluorodecanol were added to 100 mL of tetrahydrofuran, and then 0.77 g of 4-dimethylaminopyridine was added. The mixture was refluxed at 62° C. for 8 h under a nitrogen atmosphere while being vigorously stirred. The product was centrifuged, washed with alcohol, and dried to obtain modified montmorillonite.

[0076] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

[0077] The core layer is made of the following components: 50g low-density polyethylene, 14g cross-linked polyethylene, 26g cyclic polyolefin, and 6g modified montmorillonite; the bonding layer is made of the following components: 16g low-density polyethylene, 60g metallocene polyethylene, 14g cyclic polyolefin, and 0.3g diatomaceous earth; the back layer is made of the following components: 14g low-density polyethylene, 60g metallocene polyethylene, 14g cyclic polyolefin, and 0.3g diatomaceous earth.

[0078] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 30% of the total thickness; and the thickness of the back layer is 40% of the total thickness.

[0079] Example 4

[0080] A method for preparing a high-strength and high-toughness ultra-thin dry film protective film comprises the following steps:

[0081] (1) calcining montmorillonite at 500° C. in an air atmosphere for 3 h, and then cooling to room temperature to obtain activated montmorillonite;

[0082] (2) adding 10 g of activated montmorillonite and 6.5 g of hexadecylsuccinic anhydride to 100 mL of toluene, stirring and reacting for 8 h at 70° C. under a nitrogen atmosphere, and simultaneously performing ultrasonic treatment, centrifuging, washing with alcohol, and drying the product to obtain anhydride montmorillonite;

[0083] (3) 10 g of anhydride-modified montmorillonite and 9.3 g of perfluorodecanol were added to 100 mL of tetrahydrofuran, and then 0.465 g of 4-dimethylaminopyridine was added. The mixture was refluxed at 60° C. under a nitrogen atmosphere for 9 h while being vigorously stirred. The product was centrifuged, washed with alcohol, and dried to obtain modified montmorillonite.

[0084] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

[0085] The core layer is made of the following components: 40g of low-density polyethylene, 10g of cross-linked polyethylene, 20g of cyclic polyolefin, and 3g of modified montmorillonite; the bonding layer is made of the following components: 10g of low-density polyethylene, 50g of metallocene polyethylene, 10g of cyclic polyolefin, and 0.1g of diatomaceous earth; the back layer is made of the following components: 10g of low-density polyethylene, 50g of metallocene polyethylene, 10g of cyclic polyolefin, and 0.1g of diatomaceous earth.

[0086] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 30% of the total thickness; and the thickness of the back layer is 40% of the total thickness.

[0087] Comparative Example 1

[0088] A method for preparing a dry film protective film comprises the following steps:

[0089] (1) calcining montmorillonite at 600° C. in an air atmosphere for 2 h, and then cooling to room temperature to obtain activated montmorillonite;

[0090] (2) adding 10 g of activated montmorillonite and 12.9 g of hexadecylsuccinic anhydride to 100 mL of toluene, stirring and reacting for 6 h at 80° C. under a nitrogen atmosphere, and simultaneously performing ultrasonic treatment, centrifuging the product, washing with alcohol, and drying to obtain anhydride montmorillonite;

[0091] (3) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the dry film protective film.

[0092] The core layer is made of the following components: 70g of low-density polyethylene, 20g of cross-linked polyethylene, 40g of cyclic polyolefin, and 10g of anhydride-treated montmorillonite; the laminating layer is made of the following components: 30g of low-density polyethylene, 80g of metallocene polyethylene, 20g of cyclic polyolefin, and 0.5g of diatomaceous earth; the back layer is made of the following components: 30g of low-density polyethylene, 80g of metallocene polyethylene, 20g of cyclic polyolefin, and 0.5g of diatomaceous earth.

[0093] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 30% of the total thickness; and the thickness of the back layer is 40% of the total thickness.

[0094] Comparative Example 2

[0095] A method for preparing a dry film protective film comprises the following steps:

[0096] (1) calcining montmorillonite at 600° C. in an air atmosphere for 2 h, and then cooling to room temperature to obtain activated montmorillonite;

[0097] (2) The raw materials are mixed according to the formula and melted through three single-screw extruders respectively, and then formed into a film through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the dry film protective film.

[0098] The core layer is made of the following components: 70g low-density polyethylene, 20g cross-linked polyethylene, 40g cyclic polyolefin, and 10g activated montmorillonite; the laminating layer is made of the following components: 30g low-density polyethylene, 80g metallocene polyethylene, 20g cyclic polyolefin, and 0.5g diatomaceous earth; the back layer is made of the following components: 30g low-density polyethylene, 80g metallocene polyethylene, 20g cyclic polyolefin, and 0.5g diatomaceous earth.

[0099] The total thickness of the dry film protective film is less than 17 μm; the thickness of the laminating layer is 30% of the total thickness; and the thickness of the back layer is 40% of the total thickness.

[0100] The performance tests of the protective films prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were performed. The thickness of the protective film was measured with reference to GB / T 6672-2001 "Mechanical measurement method for thickness of plastic film and sheeting". The tensile strength and elongation at break of the protective film were tested with reference to GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General". The strip sampler was used for sampling. The rectangular sample length was 150±0.5 mm, the width was 15±0.5 mm, the original gauge length was set to 50 mm, and the stretching rate was set to 50 mm / min. The sample was ensured to be wrinkle-free and damaged. It was clamped vertically, and 3 parallel samples were set for each group of samples. The cup-type tester for water vapor permeability of plastic film and sheeting was used for water vapor permeability test. The water vapor permeability test was carried out by the weight gain method in the "Weight Gain and Weight Loss Method". The test temperature was 38°C, the humidity was 90% RH, the preheating time was 2h, the rotation interval was 10min, and 3 parallels were set for each group; the oxygen permeability test was carried out with reference to GB / T1038.1-2022 "Plastic Products Film and Sheet Gas Permeability Test Method Part 1: Differential Pressure Method". The test temperature was 23°C, the humidity was 50% RH, and the vacuum time was 4h. Ensure that the sample surface is free of pollution and scratches. 3 parallels were set for each group. Specific data are shown in Table 1.

[0101] Table 1 Dry film protective film performance test results

[0102]

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-strength and high-toughness ultra-thin dry film protective film, which is composed of a laminating layer, a core layer, and a back layer, wherein the core layer is located between the laminating layer and the back layer, and is characterized in that: The core layer is made of the following components by weight: 40-70 parts of low-density polyethylene, 10-20 parts of cross-linked polyethylene, 20-40 parts of cyclic polyolefin, and 3-10 parts of modified montmorillonite.

2. The dry film protective film according to claim 1, characterized in that: The molecular weight of the low-density polyethylene is 100,000 to 300,000; the molecular weight of the cyclic polyolefin is 8,000 to 30,000, and the glass transition temperature is 50 to 160° C.; the total thickness of the dry film protective film is <17 μm; the thickness of the laminating layer is 5 to 50% of the total thickness; and the thickness of the back layer is 5 to 50% of the total thickness.

3. The dry film protective film according to claim 1, characterized in that: The laminating layer is made of the following components in parts by weight: 10 to 30 parts of low-density polyethylene, 50 to 80 parts of metallocene polyethylene, 10 to 20 parts of cyclic polyolefin, and 0.1 to 0.5 parts of diatomaceous earth; the backing layer is made of the following components in parts by weight: 10 to 30 parts of low-density polyethylene, 50 to 80 parts of metallocene polyethylene, 10 to 20 parts of cyclic polyolefin, and 0.1 to 0.5 parts of diatomaceous earth.

4. The dry film protective film according to claim 1, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: (1) calcining montmorillonite and then cooling it to room temperature to obtain activated montmorillonite; (2) adding activated montmorillonite and hexadecyl succinic anhydride to toluene, stirring and reacting under nitrogen protection, centrifuging, washing with alcohol, and drying the product to obtain anhydride montmorillonite; (3) Anhydride-modified montmorillonite and perfluorodecanol are added to tetrahydrofuran, and then 4-dimethylaminopyridine is added, and the mixture is refluxed under a nitrogen atmosphere. The product is centrifuged, washed with alcohol, and dried to obtain modified montmorillonite.

5. The dry film protective film according to claim 4, characterized in that: In step (1), the calcination conditions are calcination at 500-600° C. in an air atmosphere for 2-3 hours.

6. The dry film protective film according to claim 4, characterized in that: In step (2), the ratio of activated montmorillonite to hexadecyl succinic anhydride is 10 g:6.5-12.9 g.

7. The dry film protective film according to claim 4, characterized in that: In step (2), the stirring reaction conditions are 70-80° C. for 6-8 hours, and ultrasonic treatment is performed simultaneously.

8. The dry film protective film according to claim 4, characterized in that: In step (3), the ratio of anhydride montmorillonite to perfluorodecanol is 10 g:9.3-13.9 g, and the amount of 4-dimethylaminopyridine is 5-10 wt % of the perfluorodecanol.

9. The dry film protective film according to claim 4, characterized in that: In step (3), the reflux reaction conditions are 60-65° C. for 6-9 h with strong stirring.

10. A method for preparing a high-strength and high-toughness ultra-thin dry film protective film according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the raw materials according to the formula and melting them respectively through three single-screw extruders, forming films through a batching block connector, a die head co-extrusion and cooling, and subsequently cooling and shaping the product, thickness detection, online slitting, winding and packaging to obtain the high-strength and high-toughness ultra-thin dry film protective film.

Citation Information

Patent Citations

  • Protective film for dry photosensitive film

    CN107696652A

  • Ultra-thin polyolefin dry film protective film

    CN115556450A